PELAKSANAAN PENDIDIKAN KARAKTER MELALUI SISTEM PENDIDIKAN PESANTREN (Studi di Pondok Pesantren Al-Inayah Cebolek Kidul Margoyoso Pati) - Zuhri, Muhammad Minan; *, Suparmin (Pascasarjana IAIN Kudus, 2013)
This study aimed to describe the depth of : (1 ) How does the material being taught character education in boarding school Al-InayahCebolek Margoyoso Pati Kidul ? (2) How is the implementationof character education in boarding school Al-Inayah CebolekMargoyoso Pati Kidul ? (3) What are the factors supporting andinhibiting factors in the implementation of character educationboarding school Al - Inayah Cebolek Margoyoso Pati Kidul ?This study focused on the implementation of character educationhow boarding school in Al - Inayah Cebolek Margoyoso PatiKidul?. This research includes field research (Field Research) with qualitative approaches. Data collection techniques in this study : (1) interview ( interview), (2) observation, and (3) documentation.Data analysis techniques include: (1) Reduction of Data (DataReduction), (2) Presentation of Data (Data Display) , and (3)Verification (Clonclusion Drawing). Implementation of charactereducation in boarding school Al - Inayah Cebolek Margoyoso Pati Kidul implemented submit items about religiosity, honesty,discipline, self-confidence, self-reliant, caring, responsibility,curiosity, and love for the country through exemplary method,advice, habituation, and memorization.